Hypermethylation of the oxytocin receptor gene (OXTR) in obsessive-compulsive disorder: further evidence for a biomarker of disease and treatment response. Issue 6 (3rd June 2022) - Bey, Katharina; Campos-Martin, Rafael; Klawohn, Julia; Reuter, Benedikt; Grützmann, Rosa; Riesel, Anja; Wagner, Michael; Ramirez, Alfredo; Kathmann, Norbert
ABSTRACT: Obsessive-compulsive disorder (OCD) has recently been linked to increased methylation levels in the oxytocin receptor ( OXTR ) gene, and OXTR hypermethylation has predicted a worse treatment response to cognitive-behavioural therapy (CBT). Furthermore, OCD is associated with childhood trauma and stressful life events, which have both been shown to affect OXTR methylation. Here, we aimed to replicate findings of increased OXTR methylation as a predictor of disease and worse treatment response in an independent sample that received treatment within the public health care system. In addition, we aimed to extend previous findings by examining associations between OXTR hypermethylation, environmental stressors, OCD diagnosis, and treatment response. Methylation levels at two CpGs within OXTR exon III were compared between n = 181 OCD patients and n = 199 healthy controls using linear regression analysis. In a subsample of OCD patients ( n = 98) with documented treatment data, we examined associations between methylation and treatment response to CBT. Childhood adversity and stressful life events were assessed using Childhood Trauma Questionnaire and Life Experience Survey, respectively. OCD patients exhibited significant hypermethylation at CpG site cg04523291 compared to controls, and increased methylation was associated with impaired treatment response. Moreover, hypermethylation at cg04523291 was associated with stressful life events in OCD patients, and with childhood adversity in controls. Yet, there were no significant mediation effects. In conclusion, we replicated the association between OXTR hypermethylation and OCD in the largest sample, so far. Furthermore, our findings support the role of OXTR methylation as a promising biomarker for treatment response in OCD.